2017
DOI: 10.1371/journal.pone.0168938
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mimics of Classic P-Glycoprotein Inhibitors as Multidrug Resistance Suppressors and Their Synergistic Effect on Paclitaxel

Abstract: P-glycoprotein (Pgp) is a membrane bound efflux pump spread in a variety of tumor cells and considered as a main component of multidrug resistance (MDR) to chemotherapies. In this work, three groups of compounds (imidazolone, oxazolone and vinyl dipeptide derivatives) were synthesized aiming to develop a molecular framework that effectively suppresses MDR. When tested for their influence on Pgp activity, four compounds coded Cur1-01, Cur1-12V, Curox-1 and Curox-3 significantly decreased remaining ATP concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 51 publications
2
33
0
Order By: Relevance
“…Currently, Taxol is widely used in the treatment of NSCLC in the clinics. However, many patients have acquired resistance to Taxol, and even those who initially respond will eventually exhibit MDR . We have confirmed that BZML has potent anti‐cancer activity against Taxol‐sensitive or Taxol‐resistant A549 cells through different death modes in vitro .…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Currently, Taxol is widely used in the treatment of NSCLC in the clinics. However, many patients have acquired resistance to Taxol, and even those who initially respond will eventually exhibit MDR . We have confirmed that BZML has potent anti‐cancer activity against Taxol‐sensitive or Taxol‐resistant A549 cells through different death modes in vitro .…”
Section: Discussionsupporting
confidence: 54%
“…However, many patients have acquired resistance to Taxol, and even those who initially respond will eventually exhibit MDR. [44][45][46][47] We have confirmed that BZML has potent anti-cancer activity against Taxol-sensitive or Taxol-resistant A549 cells through different death modes in vitro. 10 This paper aimed to evaluate the anticancer activity of BZML in vivo and the mechanism underlying the apoptosis resistance in BZML-treated A549/Taxol cells.…”
Section: Discussionsupporting
confidence: 53%
“…In the MTX-resistant RNOV cell line, no increased expression of P-gp or ABCB1 was observed, indicating that an atypical resistance mechanism was being observed. A previous study demonstrated that, in cancer cells resistant to cytostatics the mechanism of action of curcumin is to inhibit P-gp in a competitive or allosteric manner (41).…”
Section: Discussionmentioning
confidence: 99%
“…The synthetic pathway, described in scheme 1 utilized Erlenmeyer chemistry for azlactone synthesis. [14] In this scheme, non-commercially available cinnamic acid analogues 2 were prepared by condensation of the corresponding aldehyde with malonic acid. [15] After conversion to the hippuric acid analogues (3), cyclocondensation was affected by their reaction with the corresponding aldehydes to afford the 2-arylvinyl-4benzylidene-5-oxazolinone derivatives (azlactones, 4) under Erlenmeyer conditions.…”
Section: Chemical Synthesis Of 2-cinnamamido-n-substituted-cinnamamidmentioning
confidence: 99%
“…The compound with the highest activity in this subset was the N- (1-adamantyl) analogue (1505, Entry 4) with IC50 = 14.7 ± 0.3 µM, but with poor solubility (ClogP 6.08), while compound 1512 (Entry 2) with moderate activities (IC50 = 32.0 ± 2.6 µM) showed better solubility profile (CLogP 4.48). Importantly, 1512 showed significantly low cancer cell resistance (R-value = 8.2%), [14] and high selectivity in killing cancer cells (HCT-116, Caco-2 and HT-29) versus highly proliferative normal cells (C-166 mouse skin fibroblasts) (Figure 3). Based on 1512 favorable pharmacologic and physicochemical properties, it was selected as a new lead for the second subset of compounds (Entries 23 to 56).…”
Section: Antiproliferative Activities Of Bis-cinnamamide Derivativesmentioning
confidence: 99%